37 Risk Documentation in the Laparoscopic Cholecystectomy Consent Form. (28th February 2022) - Hassan, M.; Riad, M.
Abstract: Background: Laparoscopic cholecystectomy is one of the most common elective operations performed with a significant risk of complications. GMC guidance on consent clearly emphasises the process of informed consent and shared decision making. Failure to warn patients of a significant complication can lead to potential medico-legal implications. The effectiveness of the consent process is evidenced in fully completed consent form. Aim: We aim to access the quality of the consent forms for Laparoscopic cholecystectomy at our institution with emphasis on the documented risks. Objectives: Re-audit of quality of records of consent form documentation over one month period for laparoscopic cholecystectomy. To measure the compliance of Trust consent forms with GMC guidelines. Method: Consent forms for all elective laparoscopic cholecystectomy procedures done between July and September 2020 were obtained and retrospectively analysed. The data was collected specifically from the consent forms. A total of 39 consent forms were audited. Results: A total of 39 consent forms were audited. The majority of the consenting was done by registrars. As with the first phase, bleeding (100%), CBD injury (97.4%), bile leak (69.2%), infection (100%), damage to local structures (79.5%), VTE (94.9%) remained well documented in the written consent. Open conversion was present on 97.4% consent forms. 8 out of 16 risks audited showed a increase in compliance whereas 8 showed an decrease compared to the previous round of the audit phase. In particular, scarring, retained stones, pancreatitis, respiratory complications, diarrhoea, and cardiac complications showed a particularly low rate. Conclusions: Risk documentation on the consent forms remains quite varied. Education combined with a standardised consent form and patient information leaflet will improve the overall quality of consent forms.